Prognostic factors for chronic headache: A systematic review. (18th July 2017) - Probyn, Katrin; Bowers, Hannah; Caldwell, Fiona; Mistry, Dipesh; Underwood, Martin; Matharu, Manjit; Pincus, Tamar
Abstract : Objective: To identify predictors of prognosis and trial outcomes in prospective studies of people with chronic headache. Methods: This was a systematic review of published literature in peer-reviewed journals. We included (1) randomized controlled trials (RCTs) of interventions for chronic headache that reported subgroup analyses and (2) prospective cohort studies, published in English, since 1980. Participants included adults with chronic headache (including chronic headache, chronic migraine, and chronic tension-type headache with or without medication overuse headache). We searched key databases using free text and MeSH terms. Two reviewers independently extracted data and assessed the methodologic quality of studies and overall quality of evidence identified using appropriate published checklists. Results: We identified 16, 556 titles, removed 663 duplicates, and reviewed 199 articles, of which 27 were included in the review—17 prospective cohorts and 10 RCTs with subgroup analyses reported. There was moderate-quality evidence indicating that depression, anxiety, poor sleep and stress, medication overuse, and poor self-efficacy for managing headaches are potential prognostic factors for poor prognosis and unfavorable outcomes from preventive treatment in chronic headache. There was inconclusive evidence about treatment expectations, age, age at onset, body mass index, employment, and several headache features. Conclusions: This review identified several potential predictors of poor prognosis and worse outcome postinterventions in people with chronic headache. The majority of these are modifiable. The findings also highlight the need for more longitudinal high-quality research of prognostic factors in chronic headache.